2016
DOI: 10.1080/17449480.2016.1210181
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the European Union’s IFRS Endorsement Criteria: The Case of IFRS 9

Abstract: 2.1. The Lack of a Common TFV Interpretation under the EU's Accounting Directives 2.2. The Role of the TFV Interpretation in the IFRS Endorsement Process 2.3. The Role of the Prudence Principle for the Application of the TFV Criterion 2.4. Conclusions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…In addition, they found that the local standards less activity to increase the quality of firms' financial statements. Bischof and Daske (2016) stated that there are three criteria that could affect IFRS adoption in Europe union; this in turn could lead to affect the improvement of IFRS adoption in certain issues, such as endorsement process. Their findings showed that these three criteria improve endorsement process in Europe union firms after adopting IFRS 9.…”
Section: Ifrs Adoption In Saudi Arabia Listed Firmsmentioning
confidence: 99%
“…In addition, they found that the local standards less activity to increase the quality of firms' financial statements. Bischof and Daske (2016) stated that there are three criteria that could affect IFRS adoption in Europe union; this in turn could lead to affect the improvement of IFRS adoption in certain issues, such as endorsement process. Their findings showed that these three criteria improve endorsement process in Europe union firms after adopting IFRS 9.…”
Section: Ifrs Adoption In Saudi Arabia Listed Firmsmentioning
confidence: 99%
“…The introduction of IFRS 9 was solicited during the recent financial crisis by various international organizations, with the aim of improving accounting for financial instruments (Bischof and Daske, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…First, the private sector EFRAG discusses and advises from a technical perspective. The next steps involve a consulting by the public sector ARC on the results of those initial assessments, from a political standpoint (Bischof and Daske, 2016; Botzem, 2015; Büthe and Mattli, 2011; Walton, 2015).…”
Section: Two Benchmarksmentioning
confidence: 99%